The Urgency of Open Application Programming Interface Standardization in the Implementation of Open Banking to Customer Data Protection for the Advancement of Indonesian Banking - Billiam Billiam; Lastuti Abubakar; Tri Handayani (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2022)
Open banking with Application Programming Interface technology (open API) is an initiative that aims to streamline the payment system in Indonesia. Open API allows banks to integrate their systems with fintech and e-commerce by disclosing customer transaction data. This study aims to reveal the urgency of open API standardization in the Indonesian implementation of open banking. The study employed a normative juridical approach to secondary data. The data includes primary, secondary, and tertiary legal materials. It also used a qualitative normative data analysis method. It concludes that before the establishment of the National Standard for Open API Payment (SNAP), the process of sharing data among banks and fintech and/or e-commerce was unstandardized. It was only based on agreement among parties. Indonesian banks have different-various standards of the open API that could affect customer data protection. According to the Regulation of the Financial Service Authority Number 12/POJK.03/2018, the relationship between banks and fintech and/or e-commerce in the administration of digital banking services that is based solely on agreements among parties is not strong enough. OJK indeed presents as a supervisory agency. However, the parties will eventually return to an agreement among themselves. In contrast to the Regulation of the Financial Service Authority, the Regulation of Members of the Board of Governors, which is the legal basis for SNAP, provides standards that both service providers and service users must comply with. However, the implementation of SNAP-based open APIs still needs the readiness of personal data protection regulations.DOI: https://doi.org/10.22304/pjih.v9n1.a4